The Influence of the Organizational Justice and Trust to the Leaders on Employee Engagement with Job Satisfaction as Intervening Variable - Herminingsih, Anik (Archives of Business Research, 2017)
This study aimed to analyze the influence of organizational justice and trust to the leaders on employee engagement, with job satisfaction as an intervening variable. The research was conducted by taking samples of employees from Jabodetabek companies. Primary data were obtained by questionnaire filled by the respondents, then analyzed with simultaneous equations models and processed by AMOS program. The results showed that organizational justice has a significant effect on trust to the leaders. Organizational justice and trust to the leaders have a significant effect on employee job satisfaction. Employees' satisfaction influences significantly employee engagement, while organizational justice and trust to the leaders do not significantly influence employee engagement. It can be concluded that organizational justice and trust to the leaders do not directly influence employee engagement, but through job satisfaction as an intervening variable.